From the philosophy of language to the philosophy of meaning: An exploration of the meaning and interpretation of language - Nasrullah, Riki; Parmin, Parmin; Prayogi, Arditya (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This research addresses the complexity of the relationship between the philosophy of language, language meaning, and interpretation in a linguistic context. Philosophy of language is important in shaping contemporary linguistics through intellectual exploration. This article explores developments of thought in the philosophy of language that have enriched our understanding of language meaning. This research relates to dynamic changes in society, technology, and culture. The article is also expected to advance linguistic and philosophical theories about language and meaning in modern culture. A systematic literature review method was used to collect, evaluate, and synthesize relevant literature. The results of this study illustrate the evolution of the understanding of language and meaning from classical philosophy of language to modern philosophy of meaning. The research provides an in-depth understanding of this intellectual journey, which impacts the fields of linguistics, philosophical thinking, and cross-cultural communication.